2008
DOI: 10.1634/theoncologist.2008-0043
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma: Current Approaches and Future Directions

Abstract: After completing this course, the reader should be able to:1. Use current practice methods in the diagnosis of pheochromocytomas.2. Employ current practice methods in the treatment of pheochromocytomas.3. Evaluate the current molecular research that contributes to the treatment of pheochromocytomas.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTPheochromocytomas are rare catecholamine-secreting tumors that arise from chromaffin tissue within the adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
199
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(209 citation statements)
references
References 158 publications
6
199
0
4
Order By: Relevance
“…Clinical behavior, including invasion of adjacent tissues and the presence of metastases at non-chromaffin sites, is the only currently accepted indication of malignant pheochromocytoma [5,6]. We found that the incidence of malignant pheochromocytomas among 152 patients with pheochromocytomas was 11.2%, in good agreement with the 8% to 12.5% previously reported [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 89%
“…Clinical behavior, including invasion of adjacent tissues and the presence of metastases at non-chromaffin sites, is the only currently accepted indication of malignant pheochromocytoma [5,6]. We found that the incidence of malignant pheochromocytomas among 152 patients with pheochromocytomas was 11.2%, in good agreement with the 8% to 12.5% previously reported [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 89%
“…1,2 Pheochromocytomas are rare catecholamine-secreting tumors occurring in approximately 1-20 per million people per year in the general population. 3,4 Severe complications including hypertensive crisis, stroke and myocardial infarction are associated with pheochromocytomas. Surgical removal is the treatment of choice.…”
mentioning
confidence: 99%
“…6 The histological analysis of pheochromocytomas is not reliable for the establishment of malignancy: according to the definition by the World Health Organization, malignancy of pheochromocytomas is based on the detection of metastases. 4 Ki-67 and S100 have been suggested as possible immunohistochemical markers of malignancy, but their reliability is a matter of debate. 7,8 Pheochromocytomas are unique among other tumors, because 25-30% of them arise due to germ-line mutations related to hereditary endocrine tumor syndromes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hereditary forms often present as bilateral and multifocal neoplasms and at an earlier age than the sporadic forms. Susceptibility to develop either pheochromocytomas or paragangliomas was associated with germ mutations in some genes, for example in cases of type 2 multiple endocrine neoplasia (MEN2), type one neurofibromatosis (NF1), Von Hippel Lindau syndrome (VHL), Carney-Stratakis syndrome and genes encoding subunits B, C and D of the mitochondrial enzyme succinate dehydrogenase (SDH) 7,8 . It remains a controversial question as to whether it is necessary for all patients with pheochromocytomas/paragangliomas to be genetically tested.…”
Section: Discussionmentioning
confidence: 99%